How circuits for habits are formed within the basal ganglia - Sten Grillner (Proceedings of the National Academy of Sciences, 2025)
Recent findings show that stereotyped movement sequences (habits) need the cortex in the learning phase, but after learning, the cortex can be inactivated, and the movement still be performed flawlessly. The motor program is dependent on the sensorimotor part of the dorsolateral striatum (DLS) and on synaptic plasticity in the thalamostriatal synapses. New findings from several laboratories have revealed a highly precise spatially interactive organization within the basal ganglia [DLS, substantia nigra pars reticulata (SNr), and the thalamostriatal parafascicular nucleus (PF)] and with precise input from the cortex. The DLS-SNr-PF-DLS loop is subdivided into many parallel loops. I now propose that these parallel loops can act to reinforce the activity of the different striatal projection neurons in the DLS that take part and that the synaptic transmission in DLS becomes potentiated each time the motor sequence is performed successfully, if rewarded through a dopamine burst. It is argued that after learning the DLS-SNr-PF-DLS loop can operate in isolation.